Estimating flash flood discharge in a catchment area with the use of hydraulic model and terrestrial laser scanner - Alexakis, Dimitrios; Hadjimitsis, Diofantos G.; Agapiou, Athos (My University, 2013)
A flood can be determined as a mass of water that produces runoff on land that is not normally covered by water. This paper aims to define the potential utility of terrestrial laser scanning data and hydraulics for improving flood risk assessment models in Yialias catchment area in Cyprus. Recently, terrestrial scanners have been used to capture 3D point cloud data of high accuracy for inundation models. Thus, different methods are used to process the scanning data in order to extract hydraulically relevant information. For this reason a variety of Digital Elevation Models (DEMs) of different spatial resolution was derived. The combined use of a two dimensional (2D) numerical hydraulic model and a terrestrial laser scanner can give the opportunity of estimation of peak discharge of a recent flash flood. Hence, the approach used in this study demonstrated the potential of hydraulics and laser scanner for flood risk assessment in catchments with infrastructure and vulnerable goods.
Keywords: Point Cloud; Digital Elevation Model; Flash Flood; Terrestrial Laser Scanner; Flood Risk Assessment